STUDI HUBUNGAN SPASIAL PERSEBARAN AIRBNB DENGAN FENOMENA TURISTIFIKASI DAN GENTRIFIKASI DI KAWASAN PERKOTAAN SARBAGITA, PROVINSI BALI - Azzahra, Muthia
Sharing economy is a relatively new, progressive and innovative business, but also seen as disruption in various economic sectors—including tourism. Sharing economy inflitration in various tourism subsectors is best described by the presence of AirBnb. AirBnb’s presence can cause positive impacts on tourism revenue, yet its uncontrolled growth can also interfere societal urban structure which leads to population displacement caused by significant increase of commercial activities supporting tourism. This condition is known by the term touristification. Residential commercialisation as AirBnb may also increase property prices, which leads to displacement of indigenous population by newcomer population of higher socioeconomic status. Such condition is familiar by the term gentrification. Relationship among growth and spread of AirBnb, touristification, and gentrification can be observed on various tourism-focused regions around the world. This study is based on the urgency to identify relationships between said spread of AirBnb, touristification, and gentrification in Bali as Indonesia’s infamous tourism destination especially on Sarbagita Urban Area. Sarbagita Urban Area is planned to be formed as strategic region and tourism activity center. On this research, said relationship is obtained through global and local regression followed by formation of cluster defined by univariate spatial autocorrelation of AirBnb. Those methods will help identify spatial patterns of AirBnb, touristification, and gentrification through relationship between its variables. This study finds spatial pattern between AirBnb and touristification variables. Identification through gentrification variables also hints potential gentrification and transnational gentrification in areas where AirBnb agglomerates, which are Kuta, Denpasar Selatan, dan Ubud regions. It is recommended for related stakeholder, including planners in charge to collectively act in internalising externalities of AirBnb as ever-growing phenomenon of sharing economy.